Photoinduced charge separation in donor-acceptor spiro compounds at metal and metal oxide surfaces: Application in dye-sensitized solar cell - Macor, Lorena Paola (2012)
Modulated charge separation has been investigated by surface photovoltage spectroscopy in the fixed capacitor arrangement for four different fluorene compounds adsorbed from highly diluted solutions at ultra-thin nanoporous TiO 2 (np-TiO 2), Au and ITO surfaces. Donor (-N(C 6H 5) 2) and acceptor moieties (-CN, -COOH) were linked by fluorene or spirobisfluorene cores and the chain length has been changed by introducing thiophene. Modulated charge separation by electron injection and intramolecular transport has been separated and directed adsorption of spiro compounds at Au surfaces has been demonstrated. Striking differences between the interaction of linking -CN and -COOH groups and the different substrates were observed. The capability as TiO 2 spectral sensitizer of spirobisfluorene donor-acceptor molecules with extended conjugation has been demonstrated. Solar cells exhibit 5.6% energy conversion efficiency, confirming that spiro-configured geometry is a promising route to the design of metal free dyes. © 2012 The Royal Society of Chemistry.